Determination of temperature dependent thermophysical properties using an inverse method and an infrared line camera. (May 2016) - Zhang, Qingyu; Lippmann, Stephanie; Grasemann, Aaron; Zhu, Mingfang; Rettenmayr, Markus
Highlights: Transient heating curves are measured using an infrared camera with 512 photo diodes. A silica aerogel is used as insulation material while conducting heating experiments. Temperature dependent thermal diffusivities are determined using an inverse method. Temperature dependent specific heats are obtained by thermodynamic calculations. The determined thermal conductivities of alloys agree well with literature data. Abstract: Temperature dependent thermal diffusivities of two alloys (Al-4 wt.% Cu and 70:30 α-brass) are determined using a one-dimensional inverse method that is based on a least-square scheme. Transient temperature histories required as input for the proposed inverse method are recorded using an infrared line camera during one-sided heating or cooling. An aerogel that is transparent for infrared radiation is used as insulation material, ensuring that heat conduction is essentially one-dimensional. Temperature profiles along the samples are obtained using up to 512 photo diodes as temperature sensors. Temperature dependent specific heat capacities of the Al–Cu alloy and brass, calculated using a thermochemical library based on the CALPHAD method, are employed to calculated thermal conductivities. The calculated thermal conductivities are in good agreement with literature values. It is shown that the combination of the numerical calculations and the heating experiments provides an efficient way to determine temperature dependent thermophysical properties of alloys.